2013
DOI: 10.1097/scs.0b013e3182801866
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Gland Neoplasms in Children

Abstract: Salivary gland neoplasms in Chinese pediatric patients are rare. There is a female predominance. Most of the tumors occur among patients not younger than 10 years. The most common benign tumor is pleomorphic adenomas, and the most common malignant tumor is mucoepidermoid carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
2
14
1
2
Order By: Relevance
“…It is suggested that in the pediatric population, like in adults, the parotid gland is the most common site involved by pleomorphic adenoma. When a tumor is situated in the submandibular gland it is also mostly a benign lesion, which is not in agreement with studies on adults [2,11,12].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…It is suggested that in the pediatric population, like in adults, the parotid gland is the most common site involved by pleomorphic adenoma. When a tumor is situated in the submandibular gland it is also mostly a benign lesion, which is not in agreement with studies on adults [2,11,12].…”
Section: Discussioncontrasting
confidence: 67%
“…However, they mostly affect the parotid gland and are more common in those over ten years old, with approximately 70% occurring between 16 and 20 years of age [1]. Nevertheless the most common epithelial tumors of the major salivary glands in children and adolescents are pleomorphic adenomas (PA) [2]. However, few authors have reported the various pathological characteristics of major salivary gland tumors in children as well as adolescents and adults [3].…”
Section: Introductionmentioning
confidence: 99%
“…Mean and median age were 14.2 years (range: 1-19 years; 95% CI: 14.1-14.3 years), and female to male ratio was 1.4 (95% CI 1.3-1.4) ( Figure 1, Table 1). [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Ten studies (n = 329) reported on primary symptoms. Six of these (n = 227) reported that a solid tumor mass was present in 99% (n = 226) of children, five studies (n = 188) reported that 22% (n = 41) of children experienced pain from their tumors, and nine studies (n = 310) reported 7% (n = 22) facial nerve involvement.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The third most common type was AdCC in the parotid glands (5%; n = 21), AciCC in the submandibular glands (9%; n = 4), and adenocarcinoma (not otherwise specified) in the minor salivary glands (9%; n = 9) ( Figure 2, Supporting Information Tables S2 and S3). 11,13,14,[16][17][18][19][20][21][22][24][25][26][27][28] Grade of differentiation was only available for MEC, in a total of 11 studies (n = 182). Overall, 87% of the SGCs were of low/intermediate grade (n = 158) and 10% were of high grade (n = 18) (Supporting Information Table S4).…”
Section: Tumor Characteristicsmentioning
confidence: 99%
“…Salivary gland tumors are rare in children, with an estimated annual incidence of 0.8 per million [1,2]. About half of such tumors are malignant [2][3][4], and most are well to moderately differentiated without nodal involvement or distant metastasis [5,6]. The 5-year survival rates for pediatric patients with malignant salivary gland tumors range from 85% to 98% [1,6,7].…”
Section: Introductionmentioning
confidence: 99%